Mitigasi Dan Arahan Pengelolaan Air Asam Tambang Melalui Hutan Rawa Buatan Di Lahan Pasca Tambang - Armaiki Yusmur; Muhammad Ardiansyah; Irdika Mansur (Graduate School Bogor Agricultural University (SPs IPB), 2019)
The application of remote sensing using Unmanned Aerial Vehicle (UAV) technology to identify distribution of Acid Mine Drainage (AMD) as part of mitigation process has been done in PT. Jorong Barutama Greston. UAV imagery was interpreted visually to produce land cover map. Bare land area from land cover map is used as the boundary of the analysis area for the mitigation of AMD source. Color of soil in UAV images is used as training area for supervised classification to differentiate different pH. The result shows distribution of soil with pH between 2-3 is 1.2 ha, pH 3-4 is 4.5 ha, and pH 4-5 is 9 ha. This analysis can show that mapping results using aerial photo is effective to identify pH of soil in bare land as a source of acid to water in void and it used as input for revegetation and swamp forest planning as bio-phytoremediation efforts. Swamp forest as a wetland is one recomendation for sustainable water management on mine to increase pH and reduce heavy metal content. The success of constructed swamp forest as passive treatment for bio-phytoremediation is determined by the selection of plant species, site location, design and construction of swamp forest and maintenance. Typha latifolia, Salvinia sp., Fimbristylis globulosa, Chrysopogon zizanioides, Melaleuca leucadendra, Melaleuca cajuputi, Nauclea subdita and Nauclea orientalis L. are recom-mended as local selected plants for phytoremediation. Obtained six variables that significantly affected to determination of site location for constructed swamp forest are elevation (T), slope (S), land cover (L), cathment area (C), distance from channel (K) and distance from the monitoring pool (P). The model X = 0.2T + 0.2S + 0.1L + 0.15C + 0.3K + 0.05P applied to find very suit-able area with α = 0.05 and the R-square (R2) value 93.4%.